Nanoparticle heat transfer and fluid flow - Minkowycz, W. J.; Sparrow, E. M. (Ephraim M.); Abraham, J. P. (John P.) (Boca Raton : CRC Press/Taylor & Francis Group, 2013)
'Preface The day of nanoparticles and nanofluids has arrived, and the applications of these media are legion. Here, attention is focused on such disparate applications as biomedical, energy conversion, material properties, and fluid flow and heat transfer. The common denominator of the articles which set forth these applications here is numerical quantification, modeling, simulation, and presentation. The first chapter of this volume conveys a broad overview of nanofluid applications, while the second chapter continues the general thermofluids theme and then narrows the focus to biomedical applications. Chapters 3 and 4 deepen the biomedical emphasis. Equally reflective of current technological and societal themes is energy conversion from dispersed forms to more concentrated and utilizable forms, and these issues are treated in Chapters 5 and 6. Basic to the numerical modeling and simulation of any thermofluid process are material properties. Nanofluid properties have been shown to be less predictable and less repeatable than are those of other media that participate in fluid flow and heat transfer. Property issues for nanofluids are set forth in Chapters 6 and 7. The last three chapters each focus on a specific topic in nanofluid flow and heat transfer. Chapter 8 deals with filtration. Microchannel heat transfer has been identified as the preferred means for the thermal management of electronic equipment, and the role of nanofluids as a coolant is discussed in Chapter 9. Natural convection is conventionally regarded as a low heat-transfer coefficient form of convective heat transfer. Potential enhancement of natural convection due to nanoparticles is the focus of Chapter 10'--
Includes bibliographical references and index.
Keywords: Heat -- Transmission; Heat exchangers -- Thermodynamics; Nanoparticles -- Fluid dynamics